The Synergism Effect Of Cefepime And Vancomycin Against Coagulse Positive And Negative Methiciline Resistant Staphylococci - Curus Azimi; Hamid Choobine; Shahnam Sedigh Maroufi; Seyed Asghar Mir Emadi; Hossein Dargahi; Mohammad Kazem Sharifi Yazdi (Tehran University of Medical Sciences, 2012)
Background and Aim: Although vancomycine is used for the treatment of methicillin resistant Staphylococci, but vancomycine alone might not be effective for the treatment of methicillin resistant Staphylococci in compromised host. In the same time antimicrobial activity of cefepim on gram positive bacteria especially Staphylococci is well known. In this study the synergism effect of cefepim and vavcomycin on positive and negative coagulase Staphylococci in vitro condition was investigated. Materials and Methods: In total, 100 clinical samples of coagulase positive and negative Staphylococci were isolated from urine and blood samples from patients in Imam Khomeini Hospital during one year and identified .The modified Bauer-Kirby were used for the antibiotic susceptibility and macrodilution method for the MIC according to NCCLS procedure. Results: The results showed that after adding vancomycin to cefepime in concentration from 0.05+ 0.5 , to 0.8+8 , growth reduction reached from 3.5% to 100%.The synergism effect of the two mentioned antibiotics on coagulase negative Staphylococci resistant to methicillin were shown that from concentration of 0.05+ 0.5 to 0.8+8 , a reduction in growth from 4.5% to 100% was observed. Conclusion: The results of this study showed that vancomycin and cefepime has synergic effect on Staphylococci